Improving maternal knowledge of childhood acute respiratory infections (ARIs) in BRAC villages, Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The contribution of community-based ARI control programme of BRAC in improving maternal knowledge of acute respiratory infections in children was assessed. Data came from a cross-sectional survey of 2,938 mothers of under 5 year-old children residing in 200 randomly selected villages in two regions of Bangladesh. Three aspects of maternal knowledge such as clinical symptoms, preventive practices and home remedies were considered. While the achievement in improving knowledge had remained modest in BRAC villages, findings revealed that the programme was able to create an enable environment for change among women. The ARI promotional activities were suggested to be sensitive to the belief of mothers and their ability to understand. The chapter concludes that the ARI intervention had significance in improving maternal knowledge and points to the need of addressing more relevant issues in its intervention strategy for better performance.